Studying the phenotypic, productive and technological properties of the staple in green cotton fluff mutations - Mohammed Sadeq; Abdulkader Hussain (College of Education for Pure Sciences, 2007)
Seeds of green fuzz mutant of cotton Gossypium hirsutum L. ( Coker-31 0 ) which produced from mosaic leaves mutant (MC3) were used. The study was carried out according to complete randomize design (CRD) with three replicates. The results showed a depreciation in morphological and production properties of green fuzz mutant in comparison with white fuzz plants. The depreciation was also noticed in qualitative characters of lint.